Determinants of local government revenue and economic potential: Pathways for revenue enchancement - Riantisari, Rahmawati; Putri, Arie Rachma; Husna, Faizah Khotimatul (Optimum: Jurnal Ekonomi dan Pembangunan, 2025)
Fiscal independence represents a critical indicator of regional governments' capacity to finance development without dependence on central government transfers. Klaten Regency continues to exhibit low fiscal autonomy levels with suboptimal of local government revenue (LGR) contributions. This study aims to: a). identify principal factors influencing Klaten Regency's LGR, and b). analyze local economic potential for enhancing revenue sources. The research novelty integrates comprehensive economic factor analysis including Gross Regional Domestic Product (GRDP), population, tourist arrivals, regional taxes, regional levies, and capital expenditure with leading sector identification through Location Quotient (LQ) analysis. This holistic approach fills a significant research gap in Klaten Regency studies. The methodology employs multiple linear regression analysis of six variables, stakeholder interviews, and LQ analysis to determine base economic sectors. Results demonstrate that GRDP, population, and regional taxes have a significant influence on LGR, while tourist numbers, levies, and capital expenditure show no significant impact. Notably, levies exhibit negative effects on revenue generation. The study concludes that LGR enhancement requires optimization of base economic sectors rather than broad-spectrum approaches. Strengthening fiscal capacity demands adaptive, targeted management strategies aligned with local potential. Future research will focus on formulating tourism sector development strategies through regional business management frameworks. This comprehensive analysis provides policymakers with evidence-based insights for improving Klaten's fiscal independence through strategic economic sector development.